2007
DOI: 10.1016/j.matchar.2006.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of austenite formation during continuous heating in a low carbon steel

Abstract: The kinetics and microstructural evolution of austenite formation in a low carbon steel, with initial microstructure composed of ferrite and pearlite, were studied during continuous heating, by using dilatometric analysis and measurements of microstructural parameters. The formation of austenite was observed to occur in two stages: (a) pearlite dissolution and (b) ferrite to austenite transformation. The critical temperatures of austenite formation in continuous heating increase with increasing heating rate, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
47
0
19

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(80 citation statements)
references
References 9 publications
(18 reference statements)
2
47
0
19
Order By: Relevance
“…Previous studies 13 have shown that these mechanisms can depend on the heating rates. Dilatometry has been largely used for studies of phase transformations on several types of steels 14 , such as low-carbon steels 15 and maraging steels 13,16 . In this work the dilatometric technique was used to study the influence of chemical composition on precipitation and the martensite reversion phenomena, as well as to evaluate the activation energies of these phase transformations during the heating stage.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies 13 have shown that these mechanisms can depend on the heating rates. Dilatometry has been largely used for studies of phase transformations on several types of steels 14 , such as low-carbon steels 15 and maraging steels 13,16 . In this work the dilatometric technique was used to study the influence of chemical composition on precipitation and the martensite reversion phenomena, as well as to evaluate the activation energies of these phase transformations during the heating stage.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these studies use commercial dilatometry equipment to determine transformation kinetics through dilatometric specimens of different shapes and sizes, for example, solid cylindrical shape, hollow, or flat in small sizes, ensuring that the changes in volume obtained are due solely to the phase transformation or the internal changes in the material and not to distortion caused by the thermal shock in the heating and quenching stages. Likewise, the dilatometry devices can use different heating media such as magnetic induction, thermal radiation, and direct current or Joule heating [3], [7] and [8]. This latter medium is characterized by providing thermal homogeneity in the material and good control of the heating rate (HR), which can remain constant for the whole heating stage.…”
Section: Introductionmentioning
confidence: 99%
“…El análisis teórico de las temperaturas producidas por el proceso de temple superficial con láser ha dado lugar a numerosos trabajos que abarcan desde la utilización de modelos simplificados como en Cordovilla-Baró et al (2014), hasta modelos tridimensionales basados en el método de los elementos finitos (García-Beltrán et al, 2007;Leung et al, 2007;Oliveira et al, 2007;García-Beltrán et al, 2008;Bailey et al, 2009). Sin embargo, estos trabajos, o bien utilizan un valor constante para caracterizar la absorción, o bien plantean el incremento de absorción asociado a la oxidación como una función de la temperatura instantánea.…”
Section: Introduccionunclassified